Morphological characteristics of dolphinfish Coryphaena hippurus Linnaeus 1758 landed in Kalinaun Village, East of Likupang District, North Sulawesi - Mantiri, Nicola R. K.; Tilaar, Ferdinand F.; Pratasik, Silvester B.; Sinjal, Henky; Lohoo, Anneke V.; Rondonuwu, Ari B. (Jurnal Ilmiah Platax, 2023)
This study aimed to determine the size group of fish caught, compare the morphometric characteristics between sexes, and describe the meristic characteristics of the dolphinfish Coryphaena hippurus. This study used a descriptive method. The morphometric characteristics were measured using a ruler and tape at the accuracy of 1 mm and 5 m, respectively, while the meristic characteristics were obtained by counting the number of spines. This study found a total of 57 individuals of the dolphinfish that had a size range of 48–89 cm, the male from 48 to 95 cm, and the females from 49 to 84 cm, respectively. Four morphometric parameters of male and 2 parameters of female dolphinfish could be used to predict the total length. The dolphinfish also had 59 dorsal soft rays, 25 soft pelvic rays, 22 soft pectoral rays, 26 soft anal rays, and 48 hard caudal rays. Keywords: descriptive, morphometric, meristic, size. Abstrak Penelitian ini bertujuan untuk mengetahui kelompok ukuran ikan yang tertangkap, membandingkan karakteristik morfometrik antar jenis kelamin, dan mendeskripsikan karakteristik meristik ikan Lemadang Coryphaena hippurus. Penelitian ini menggunakan metode deskriptif. Karakteristik morfometrik diukur menggunakan penggaris dan meteran dengan ketelitian masing-masing 1 mm dan 5 m, sedangkan perhitungan meristik dilakukan dengan cara menghitung jari-jari sirip. Penelitian ini menemukan sebanyak 57 individu ikan Lemadang yang memiliki kisaran ukuran 48-89 cm, jantan 48-95 cm, dan betina berkisar 49-84 cm. Empat parameter morfometrik ikan Lemadang jantan dan 2 parameter ikan lemadang betina dapat digunakan untuk menduga panjang total. Ikan Lemadang juga memiliki 59 jari-jari lemah sirip punggung, 25 jari-jari lemah sirip perut, 22 jari-jari lemah sirip dada, 26 jari-jari lemah sirip dubur, dan 48 jari-jari keras sirip ekor. Kata kunci: deskriptif, morfometrik, meristik, ukuran.